Effect of type and concentration of organic acids on the extraction efficiency of glutamic acid and bioactive compounds from sipou (Siphonosoma australe-australe) - Yusuf, Muhammad; Hardiwinoto; Rosli, Siti Zaharah; Diode Yonata; Boby Pranata; Siti Zaharah Rosli (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
Sipou (Siphonosoma australe-australe) is a marine mollusk abundant in Indonesian waters, but its utilization is still limited. Sipou contains glutamic acid and has antioxidant activities that can be extracted with acid. This study aimed to determine the optimal type and concentration of organic acids for extracting glutamic acid and bioactive compounds from sipou. The study used a completely randomized factorial design (RALF)with treatments of organic acid types (lactic, acetic, and citric acid) and concentrations (1%, 3%, and 5%) with three replications. The results showed that the type and concentration of organic acids significantly affected the levels of protein and glutamic acid, antioxidant activity, and color characteristics (p<0.05). Treatment with 3% citric acid resulted in the highest glutamic acid content (6.15 mg/100 mL) and strong antioxidant activity, while also providing a more concentrated extract color compared to other solvents. This advantage is related to the ability of citric acid to break down protein structures and maintain the stability of the bioactive compounds. Thus, 3% citric acid is recommended as the optimal solvent for obtaining high-quality sipou extract that has the potential for application in the functional food and pharmaceutical industries.